2=6t40+t

Rewrite the equation as 6t40+t=2.

6t40+t=2

Multiply each term by 40+t and simplify.

Multiply each term in 6t40+t=2 by 40+t.

6t40+t⋅(40+t)=2⋅(40+t)

Cancel the common factor of 40+t.

Cancel the common factor.

6t40+t⋅(40+t)=2⋅(40+t)

Rewrite the expression.

6t=2⋅(40+t)

6t=2⋅(40+t)

Simplify 2⋅(40+t).

Apply the distributive property.

6t=2⋅40+2t

Multiply 2 by 40.

6t=80+2t

6t=80+2t

6t=80+2t

Move all terms containing t to the left side of the equation.

Subtract 2t from both sides of the equation.

6t-2t=80

Subtract 2t from 6t.

4t=80

4t=80

Divide each term by 4 and simplify.

Divide each term in 4t=80 by 4.

4t4=804

Cancel the common factor of 4.

Cancel the common factor.

4t4=804

Divide t by 1.

t=804

t=804

Divide 80 by 4.

t=20

t=20

t=20

Solve for t 2=(6t)/(40+t)